2018
DOI: 10.1155/2018/9293623
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Damage Mechanism Induced by Earthquake in a Plate Girder Bridge Based on Seismic Response Analysis: Case Study of Tawarayama Bridge under the 2016 Kumamoto Earthquake

Abstract: This paper reports a damage survey and seismic analysis of a bridge. In the first part, the damage survey of some bridges that were affected by the 2016 Kumamoto Earthquake was discussed. Among these bridges, the Tawarayama Bridge, which is a plate girder bridge located very close to an active fault line, was particularly considered. This bridge incurred severe damage because of the earthquakes’ epicenters very close to the bridge. The damage mechanism that can occur in this type of bridge was elucidated. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It can be confirmed that it is very inappropriate to ignore the role of the lower lateral bracing when analyzing seismic damage to steel bridges, especially in relation to seismic pounding damage. In previous studies [16,17], the lower lateral bracing was also considered in the simulations, albeit simplified to ancillary components. Simplification of the bracing is generally considered only as beam elements in the finite element model, rather than refined plate elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be confirmed that it is very inappropriate to ignore the role of the lower lateral bracing when analyzing seismic damage to steel bridges, especially in relation to seismic pounding damage. In previous studies [16,17], the lower lateral bracing was also considered in the simulations, albeit simplified to ancillary components. Simplification of the bracing is generally considered only as beam elements in the finite element model, rather than refined plate elements.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al [15] evaluated the pounding interaction between bridge abutments and steel beams under nonuniform seismic excitation. Aye et al [16] discussed the damage survey of the Tawarayama Bridge affected by the Kumamoto earthquake, especially about its lower lateral bracing's severe damage by the earthquake. Mustafa and Miki [17] found that the bottom plate of the end steel beam will rotate inward under the action of an earthquake and damage will occur at the connection with lower lateral bracing.…”
Section: Introductionmentioning
confidence: 99%
“…Nozu and Nagasaka (2017) simulated the rupture processes of the mainshock based on the strong ground motion data and proposed that the slip deficit at a deeper part beneath Mashiki town likely caused the generation of large ground motions. A previous damage assessment of infrastructures conducted by Aye et al (2018) reported bridge collapses at the western Aso flank. By using optical satellite images, a concentration of numerous landslides and soil avalanches were identified around the caldera rim and central cone of Aso volcano (Xu et al, 2018).…”
Section: 1029/2020ea001200mentioning
confidence: 96%
“…In addition, buckling and disconnection of stiffeners and lateral braces appeared. Mya Nan et al [ 8 ] investigated the severely damaged Tawarayama Bridge, particularly the buckling of the lower lateral members, suggesting that the buckling design of the lower lateral members should be considered. Gibe et al [ 9 ] discussed the failure process and limit state of steel bearings in the Kumamoto earthquake, especially under loads in the vertical bridge axis.…”
Section: Introductionmentioning
confidence: 99%